COVID-19’s Direct and Indirect Impact - Irma Ruslina Defi (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
The COVID-19 outbreak has been declared a public health emergency of worldwide concern by theWorld Health Organization. The direct and indirect effects of COVID-19 on health and well-beingare still being investigated. In addition to the direct impacts of COVID-19 disease, social distancingand lockdown measures have had a significant and unequal effect on individuals, households, andcommunities through restrictions imposed on our daily social an d economic activities.